(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The national security system of the Republic of Montenegro is based upon the specifics of the Montenegrin country and is adjusted in such a manner that is able to respond to the contemporary security challenges. That said, it has to address to a great extent the threats and risks which the country faces on a national, regional and international plan. This signifies building an efficient system, functional and operative, for dealing with security threats to the country. The basic dilemmas which are subject of discussion in the paper itself refer to the issues “Whether the national security system could completely enforce the national security policy?” as well as the question “Whether Montenegro, because of the limited resources, has the adequate capacities for dealing with the security risks and threats?” These issues are always in the open row for which new answers are looked for.